Perception of oil palm smallholders toward intercropping system: a case study at Merlimau, Melaka / Shahrul Nazrin Saidin - Saidin, Shahrul Nazrin (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, intercropping system is a very popular application among oil palm smallholders. Nowadays, not many oil palm smallholders that apply the intercropping system at their field because the cost of practicing the intercropping system is high. Other than that, intercropping is not practiced by most farmers because the results of intercropping can be uncertain. The objectives of this study are to examine the relationship between factors that influences the perception of oil palm smallholders toward perception of intercropping system and to determine the most dominant factor that influence the perception of oil palm smallholders toward intercropping system. This study was conducted to the 63 oil palm smallholders at Merlimau, Melaka. The sampling method used in this study is Simple Random Sampling (SRS). The independent variables in this study are profit, cost, knowledge and social influence. While, the dependent variable in this study is the perception of oil palm smallholders toward intercropping system. There are two analysis testing used in this study to achieve the objectives of this study, which are correlation analysis test and multiple regression analysis test. Result of correlation analysis test were showed; profit (0.578), cost (0.640), knowledge (0.799), and social influence (0.335) have a significant relationship with the perception of oil palm smallholders toward intercropping system. From the multiple regression analysis, the result were shown that knowledge factor was the most dominant factor that influenced the perception of oil palm smallholders toward intercropping system. In conclusion, all independent variable factors in this study influenced the perception of oil palm smallholders toward intercropping system. For the recommendation, it is recommended for the government agency should give more subsidies to the oil palm smallholders to encourage in practicing the intercropping system in their field.